DRUG UTILIZATION STUDY FOR AZILSARTAN MEDOXOMIL IN GERMANY. (June 2018) - Ehlken, B.; Shlaen, M.; Lopez Fuensalida Torres, M.P.; Hisada, M.; Bennett, D.
Abstract : Objective: To evaluate azilsartan medoxomil (AM) utilization patterns in the primary care setting in Germany. Design and method: This is a retrospective cohort study among patients initiated on AM in the primary care setting in Germany from 01/2012 to 12/2013 (first wave) and 01/2014 to 11/2016 (second wave) using a patient-level electronic medical records database. Scientific data Prescription patterns—including patient demographics, off label use, use in patient populations with missing information, concomitant use of other antihypertensive drugs and drugs that may cause drug-drug interactions with AM—were analysed using the primary care physician panel of the IMS® Disease Analyzer database. Results: A total of 852 of 1, 159 (74%) and 696 of 811 patients (86%) met the inclusion criteria for the first and second waves of analysis (activity in database 12 months before and 6 months after first AM prescription), respectively. In both analyses, approximately 25% of patients (first wave: 23%, second wave: 24%) were aged 75 years or older and one patient (first wave) was younger than 18 years of age; 50% (first wave) and 46% (second wave) were females. AM was prescribed for the label indication (essential hypertension) in 83% (first wave) and 68% (second wave) of patients. Indication for use was missing in 12% (first wave) and 26% (second wave) of patients. Simultaneous prescription of AM with other antihypertensive drugs at exposure start of AM was recorded in 23% (first wave) and 37% (second wave) of patients. Drugs that might cause a drug interaction with AM were simultaneously prescribed in 3% of the study population in both waves; overlapping prescription periods at AM exposure start were detected in 14% (first wave) and 8% (second wave) of patients initiated on AM. Conclusions: The results of the study show that AM has been used in the appropriate population for the approved indication in patients aged 18 years or older. Concomitant use with drugs that may cause a drug interaction decreased substantially during the second wave period. Use of dual RAAS blockade therapies was low in this population, which considerably decreased during the study.